Development of push moraines in deeply frozen sediment adjacent to a cold‐based glacier in the McMurdo Dry Valleys, Antarctica. Issue 3 (20th December 2019) - Fitzsimons, Sean; Howarth, Jamie
Abstract: Previous studies of push moraines have concluded that structural architecture is controlled by a combination of stress exerted by flowing ice and the rheology of the deforming sediment. However, the relationship between deformation processes and the thermal/hydrologic conditions within the sediment remains ambiguous. Using a combination of surface mapping, logging exposures and ground penetrating radar we examine the relationships between surface morphology, material properties and development of deformation structures in deeply frozen sediment that has been deformed by Joyce Glacier, a cold‐based glacier in the McMurdo Dry Valleys. The structural architecture of the push moraines is characterized by a combination of brittle and ductile deformation structures that have produced a structurally complex pattern of thrust faults, low angle listric thrusts and recumbent folds that extend 400 m beyond the glacier margin. Deformation is ductile where the ice concentration exceeds c . 65% volume and predominantly brittle where the ice concentration is less than c . 65%. The change in rheology reflects transition in behaviour from the material having a predominantly frictional character when the ice is limited to pore spaces to a non‐frictional character in which strength is primarily determined by the cohesive strength of the ice. This work shows that glaciotectonic deformation can occur in deeply frozen permafrost where there is no liquid pore water. We conclude that the presence of liquid porewater is not a necessary condition for the development of glaciotectonic deformation or for the formation of push moraines. © 2019 John Wiley & Sons, Ltd. Abstract : Deformation of proglacial permafrost at the margin of a cold‐based Antarctic glacier is characterised by a combination of brittle and ductile deformation controlled by the rheology of the deforming materials. Cold‐based glaciers that flow over permafrost are likely to leave a strong glacitectonic imprint in the landscape.